If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(2) + -4 = 2x + 4 Multiply 6 * 2 12 + -4 = 2x + 4 Combine like terms: 12 + -4 = 8 8 = 2x + 4 Reorder the terms: 8 = 4 + 2x Solving 8 = 4 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 8 + -2x = 4 + 2x + -2x Combine like terms: 2x + -2x = 0 8 + -2x = 4 + 0 8 + -2x = 4 Add '-8' to each side of the equation. 8 + -8 + -2x = 4 + -8 Combine like terms: 8 + -8 = 0 0 + -2x = 4 + -8 -2x = 4 + -8 Combine like terms: 4 + -8 = -4 -2x = -4 Divide each side by '-2'. x = 2 Simplifying x = 2
| -0.8-41.6=0.40 | | x^2+4x=-3x-6 | | 4.6(4+2x)-4.4=14 | | 75=9c-6 | | -8x+2-16=-5x+7x | | 15+5(z-3)=4x+3 | | -0.8x+0.8(-52)=0.40 | | 5d=2d-9 | | 0.3y=-15.6 | | 4(x+3)+8=4x+20 | | (2n)+4=20 | | 0.3y=15.6 | | 6d=3d+15 | | 3(2x-4)+3x=33 | | -0.8x-26=16 | | 8n-9=-10 | | 39x^4+34x^2-26=0 | | -23+4=m-5 | | 4x+20=12x+60 | | 2x^2-a-13=2 | | t^3-3t-2=0 | | -20-8x=-11x+22 | | x=(0.03x+0.03) | | 2*n=1.20 | | 2x+26=x+4 | | 4x+12-2x=56 | | -4m-8=-4 | | 3(4x-2)=12z | | y=2x^2-7 | | -25x+50=75x-1150 | | 300+10x=20x-600 | | 20logx=21 |